Treatment strategy for insomnia disorder: Japanese expert consensus - Takaesu, Yoshikazu; Sakurai, Hitoshi; Aoki, Yumi; Takeshima, Masahiro; Ie, Kenya; Matsui, Kentaro; Utsumi, Tomohiro; Shimura, Akiyoshi; Okajima, Isa; Kotorii, Nozomu; Yamashita, Hidehisa; Suzuki, Masahiro; et al. (Frontiers in Psychiatry, 2023)
Purpose: There is a lack of evidence regarding answers for clinical questions about treating insomnia disorder. This study aimed to answer the following clinical questions: 1) how to use each hypnotic and non-pharmacological treatment differently depending on clinical situations and 2) how to reduce or stop benzodiazepine hypnotics using alternative pharmacological and non-pharmacological treatments. Methods: Experts were asked to evaluate treatment choices based on 10 clinical questions about insomnia disorder using a nine-point Likert scale (1=“disagree” to 9=“agree”). The responses of 196 experts were collected, and the answers were categorized into first-, second-, and third-line recommendations. Results: The primary pharmacological treatment, lemborexant (7.3±2.0), was categorized as a first-line recommendation for sleep initiation insomnia, and lemborexant (7.3±1.8) and suvorexant (6.8±1.8) were categorized as the first-line recommendations for sleep maintenance insomnia. Regarding non-pharmacological treatments for primary treatment, sleep hygiene education was categorized as the first-line recommendation for both sleep initiation (8.4±1.1) and maintenance insomnia (8.1±1.5), while multicomponent cognitive behavioral therapy for insomnia was categorized as the second-line treatment for both sleep initiation (5.6±2.3) and maintenance insomnia (5.7±2.4). When reducing or discontinuing benzodiazepine hypnotics by switching to other medications, lemborexant (7.5±1.8) and suvorexant (6.9±1.9) were categorized as first-line recommendations. Conclusion: Expert consensus indicates that orexin receptor antagonists and sleep hygiene education are recommended as first-line treatments in most clinical situations to treat insomnia disorder.